Estimation of Performance of the H Wind Turbine Using the Multiple Double Disk Stream Tube Theory - Mesbah. M. Salem; Ali Mohamed Elmabrok (Surman Journal of Science and Technology, 2024)
The performance of the H vertical axis turbine is comparable with that of the more common horizontal axis machines. It has a number of aerodynamic and structural advantages over HAWT'S. However, the H straight blade turbine is not self- starting at low wind speeds which is a considerable disadvantage for a simple small-scale installation. Generally, papers concerning vertical axis turbine do not study the behavior of the rotor at low tip speed ratios. Therefore, they do not deal with the self-starting problem. A number of analytical methods were investigated to see whether they could predict the starting performance of vertical axis turbines. The Chosen methods used “actuator disc theory" for multiple Stream tubes. In this paper the multiple stream tube model is applied using two discs in tandem. The computational analysis of all models simulates the blade aerodynamics throughout the full range of incidence from -180° to 180°. The effects of varying various geometric parameters of the windmill upon the performance of the rotor are investigated to find a design with improved self-starting characteristics.